HYBRID CLOUD ARCHITECTURE: IN PHARMACEUTICAL DEVELOPMENT AND MANUFACTURING. - ANBIL, PARTHA S. (Pharmaceutical Technology)
The article focuses on how hybrid cloud architecture enables pharmaceutical and biotechnology organizations to accelerate drug development while maintaining regulatory compliance and protecting intellectual property. It explains that hybrid cloud combines the scalability of public clouds with the security and control of private infrastructure, addressing stringent regulations such as FDA 21 CFR Part 11 and emerging AI governance frameworks from the FDA and European Medicines Agency. The article details hybrid deployment patterns—such as data residency tiering, federated learning, and cloudbursting—that optimize workload segmentation based on data sensitivity and computational needs across drug discovery, clinical trials, manufacturing, and supply chain management. It also highlights industry examples, including the collaboration between Eli Lilly and NVIDIA, demonstrating how hybrid cloud supports Pharma 4.0 initiatives and global regulatory adherence. The article concludes that successful hybrid cloud adoption requires organizational capability development and a graduated implementation approach to balance innovation with compliance and data integrity.